2021
DOI: 10.21873/anticanres.15205
|View full text |Cite
|
Sign up to set email alerts
|

TrkB/BDNF Signaling Could Be a New Therapeutic Target for Pancreatic Cancer

Abstract: Background/Aim: Tropomyosin-related kinase B (TrkB)/brain-derived neurotrophic factor (BDNF) signaling plays a role in inducing malignant phenotypes in several aggressive types of cancers. To create a conclusive therapy targeting TrkB/BDNF signaling in solid refractory cancers, the biological significance of TrkB/BDNF signaling was analyzed in pancreatic ductal adenocarcinoma (PDAC) cells. Materials and Methods: Three PDAC cell lines were used as target cells to investigate proliferation and invasiveness. Smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Matrix metallopeptidase-9 (MMP-9) has been widely associated with cancer pathology (Huang, 2018). S100A9 is an oxidative stress gene (Saheb Sharif-Askari et al, 2021), and Lv et al (2020) found that S100A9 enhances prostate cancer cell invasion by activating TLR4/NF-κB/integrin β1/FAK signaling. Chen et al (2021) found that β-sarcoglycan (SGCB) is a prognostic metabolism-related gene in clear-cell RCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix metallopeptidase-9 (MMP-9) has been widely associated with cancer pathology (Huang, 2018). S100A9 is an oxidative stress gene (Saheb Sharif-Askari et al, 2021), and Lv et al (2020) found that S100A9 enhances prostate cancer cell invasion by activating TLR4/NF-κB/integrin β1/FAK signaling. Chen et al (2021) found that β-sarcoglycan (SGCB) is a prognostic metabolism-related gene in clear-cell RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) is a potent neurotrophic factor ( Numakawa et al, 2018 ) that promotes breast cancer cell growth and metastasis ( Tajbakhsh et al, 2017 ). Oyama et al revealed that tropomycin receptor kinase B (TrkB)/BDNF signaling could be a novel therapeutic target in pancreatic cancer ( Oyama et al, 2021 ). Liu et al (2009) found that Fas ligand (FASLG) polymorphisms were correlated with cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study uncovered a link between the ability of glioblastoma to make less invasive cancer cells around them more aggressive via the transfer of TrkB-containing exosomes, revealing this way a mechanism by which these tumours can influence their environment to promote disease progression and aggressiveness (Pinet al et., 2016), while other reports have shown that inhibition of TrkB-associated signaling may be an effective strategy to limit the formation of astrocytomas (Ni et al, 2017) as well as the survival of glioblastoma cancer cells (Pinheiro et al, 2017). Finally, emerging evidence suggest that TrkB signaling could also be a therapeutic target for other cancer types, including lung (Sinkevicius et al, 2014; Chen et al, 2016), breast (Choy et al, 2017; Contreras-Zárate et al, 2019), and pancreatic cancer (Oyama et al, 2021). Taken together, these studies suggest that targeting TrkB signaling with cannflavins may provide therapeutic benefits against these cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, 3D imaging of PanIN lesions allowed visualisation of glial activation in an early stage of tumorigenesis and demonstrated a 5-fold increase in GFAP+ fibers [ 159 ]. Furthermore, many soluble factors of neurotrophic or axon-guiding nature such as NGF [ 147 , 160 ], brain-derived neurotrophic factor (BDNF) [ 147 , 161 ], neurotrophin 3 (NT-3) [ 147 , 162 ], glial-cell-derived neurotrophic factor (GDNF) [ 163 ], neurturin [ 164 ], artemin [ 165 , 166 ], sonic hedgehog [ 167 , 168 ], SEMA3D [ 169 ], and others are overexpressed by pancreatic tumour cells. SCs are well known to express the same factors in injury settings [ 43 ].…”
Section: Schwann Cell Involvement In Physiology and Disorders Of The ...mentioning
confidence: 99%